Preparation for The ASEAN Economic Community of Educational Institutes: Case study in Thai and Indonesian Private Nursing Institutions - Artsanthia, Jintana; Suyasa, I Gede Putu Darma; Susanti, Ni Luh Putu Dina (Journal of The Royal Thai Army Nurses, 2017)
The objectives of the study of preparation for the ASEAN economic community of educational institutes were to 1) explore inhibitors and enabling factors of education management of nursing schools 2) share information in Preparing for the ASEAN Economic Community. Sample size composed of 100 studentsand 20 educational committeeof nursing schools.This study employed a qualitative approach using SWOT analyses framework to identify enablers and inhibitors. Semi structured interview among the administrative staff and policy makers in focus Group.Data analysis was used by content analysis.The result was shown that educational institutions should clear strategy and the inhibitors of educational management were English skill competency, technology to support, lack of facility and research focus, collaboration skill to contact among ASEAN community, networking in collaboration among ASEAN community and the enabling factors of institute should have MOU with universities, collaboration, scholarship for students and staffs, joint research with foreign institutions, adequate funding to support, establishing international collaboration. In preparing the institute shouldprovide training on languages, especially an Englishlanguage and the language of neighboring countries. The push for comprehensive ASEAN studies, which cover the following areas: basic knowledge of ASEAN member states about the different rules and regulations within ASEAN member countries; knowledge in the 21stcentury model by accelerating the setting up of standards and revise new learning processes, develop graduates’ skills of nursing according to ASEAN and international standards. Thepush for educational cooperation between Thailand and other ASEAN member states, which yields concrete results and which can truly contribute towards development. Accelerate and increase information output through various medias and ICT in preparation for the ASEAN Community for nursing educational institutes. การเตรียมความพร้อมของสถาบันการศึกษาในการเข้าสู่ประชาคมอาเซียน: กรณีศึกษาสถาบันการศึกษาพยาบาลเอกชนของไทยและอินโดนีเซีย การศึกษาการเตรียมความพร้อมในการเข้าสู่ประชาคมอาเซียนของสถาบันการศึกษานี้มีวัตถุประสงค์เพื่อศึกษาปัจจัยที่เป็นปัญหาอุปสรรคในการบริหารจัดการของสถาบันการศึกษาพยาบาล และเพื่อศึกษาการใช้ประโยชน์จากข้อมูลสารสนเทศในการเตรียมความพร้อมเข้าสู่ประชาคมอาเซียน เป็นการศึกษาเชิงคุณภาพ กลุ่มตัวอย่างเป็นนักศึกษาพยาบาล 100 คน ผู้บริหารทางการพยาบาลจำนวนรวม 20 คน ใช้กรอบการวิเคราะห์ของ SWOT ในการหาปัจจัยปัญหาอุปสรรคในการเตรียมความพร้อมสู่ประชาคมอาเซียน โดยการสัมภาษณ์เจาะลึก ทำกลุ่ม กับนักศึกษาและผู้บริหารสถาบันที่มีส่วนเกี่ยวข้องในการกำหนดนโยบายของสถาบันใช้การวิเคราะห์เนื้อหา (content analysis) ผลการวิจัยพบว่าสถาบันการศึกษาควรวางกลยุทธ์ให้ชัดเจนในการเตรียมความพร้อมสู่ประชาคมอาเซียน ส่วนปัญหาอุปสรรคในการเตรียมความพร้อมของการเข้าสู่ประชาคมอาเซียนคือการพัฒนาทักษะการใช้ภาษาอังกฤษ การส่งเสริมการพัฒนาตนเองอย่างจริงจัง การขาดบุคลากร ขาดงานวิจัยที่สนับสนุน ส่วนด้านปัจจัยเอื้อในการเตรียมความพร้อมในการเข้าสู่ประชาคมอาเซียน ควรมีความร่วมมือการสร้างเครือข่ายความร่วมมือของสถาบันการศึกษาการลงนามความร่วมมือจึงเป็นทางเลือกหนึ่งที่จะให้มีการพัฒนาภาษาอังกฤษการสนับสนุนทุนแลกเปลี่ยนอาจารย์นักศึกษา ความร่วมมือทางการวิจัยของสถาบันจะทำให้เกิดการผลักดันในประเด็นต่างๆ เพื่อให้เกิดการศึกษาอาเซียนที่ครอบคลุมความรู้พื้นฐานเกี่ยวกับกฎข้อบังคับของประเทศสมาชิกอาเซียน การเรียนรู้ในศตวรรษที่ 21 โดยการกระตุ้นผ่านการใช้เทคโนโลยีสารสนเทศด้วยวิธีการที่หลากหลายผ่านสื่อต่างๆ จึงเหมาะกับการเตรียมความพร้อมในการเข้าสู่ประชาคมอาเซียนของสถาบันการศึกษาพยาบาล